Wood and metal shear wall formwork and its performance concerning its uses number and costs - Aguilar Huerta, Jose Ronald; Barreto Rivera, Urpi; Berrio Atapauccar, Lisbeth (Universidad Ciencia y Tecnología, 2023)
Concrete construction requires a formwork that shapes the structural sections and resists the concrete’s weight, representing between 40% and 60% of the overall concrete costs, so the construction team must make cost-effective decisions throughout the project. This research compares the technical and economic performance, unit cost, and the number of metal and wood formwork applications in constructing shear walls in 80 single-family units assembled in 4 real estate units. To reach the yield value of 3,501.18m2, with the metal formwork, 31 uses were required at the cost of 5,873.13 USD; on the other hand, with the wood formwork, 51 uses were necessary at the cost of 14,289.79 USD. After 20 uses, comparing the wood formwork with the metal formwork, the latter was 66% more efficient.